Development of 3D imaging technique of reconstructed human epidermis with immortalized human epidermal cell line. Issue 5 (6th June 2018) - Inoue, Yu; Hasegawa, Seiji; Miyachi, Katsuma; Yamada, Takaaki; Nakata, Satoru; Ipponjima, Sari; Hibi, Terumasa; Nemoto, Tomomi; Tanaka, Masahiko; Suzuki, Ryo; Hirashima, Naohide
Abstract: The epidermis, the outermost layer of the skin, retains moisture and functions as a physical barrier against the external environment. Epidermal cells are continuously replaced by turnover, and thus to understand in detail the dynamic cellular events in the epidermis, techniques to observe live tissues in 3D are required. Here, we established a live 3D imaging technique for epidermis models. We first obtained immortalized human epidermal cell lines which have a normal differentiation capacity and fluorescence‐labelled cytoplasm or nuclei. The reconstituted 3D epidermis was prepared with these lines. Using this culture system, we were able to observe the structure of the reconstituted epidermis live in 3D, which was similar to an in vivo epidermis, and evaluate the effect of a skin irritant. This technique may be useful for dermatological science and drug development.